2011
DOI: 10.1002/ijc.26447
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive T cell therapy promotes the emergence of genomically altered tumor escape variants

Abstract: Adoptive T cell therapy has proven effective against melanoma in mice and humans. However, because most responses are incomplete or transient, cures remain rare. To maximize the efficacy of this therapy, it will be essential to gain a better understanding of the processes which result in tumor relapse. We studied these processes using B16ova murine melanoma and adoptive transfer of OT-I T cells. Transfer of T cells as a single therapy provided a significant survival benefit for mice with established subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 35 publications
4
56
2
Order By: Relevance
“…2B). According to earlier reports (22,23), using even higher cell numbers in adoptive transfer does not translate into long-term survival of B16.OVA-bearing mice, highlighting the immunosuppressive nature of the model, which is in accord with clinical observations suggesting a lack of efficacy in T-cell therapies used as single agents for the treatment of solid tumors. Keeping in mind that human adenovirus does not productively replicate in or lyse murine B16.OVA cells, the observed synergy between adenovirus and the transferred T cells was likely the result of favorable immune responses instigated by infection per se.…”
Section: Adenovirus Treatment Enhances the Efficacy Of Adoptive T-celmentioning
confidence: 56%
“…2B). According to earlier reports (22,23), using even higher cell numbers in adoptive transfer does not translate into long-term survival of B16.OVA-bearing mice, highlighting the immunosuppressive nature of the model, which is in accord with clinical observations suggesting a lack of efficacy in T-cell therapies used as single agents for the treatment of solid tumors. Keeping in mind that human adenovirus does not productively replicate in or lyse murine B16.OVA cells, the observed synergy between adenovirus and the transferred T cells was likely the result of favorable immune responses instigated by infection per se.…”
Section: Adenovirus Treatment Enhances the Efficacy Of Adoptive T-celmentioning
confidence: 56%
“…For several reasons, however, this approach has proven more challenging, including the facts that (1) real self-tumor antigens are relatively weak as the host is tolerized towards them and contains very few T-cell precursors (39); (2) the selective pressure applied by immune therapies towards a single tumor antigen can lead to escape variants (44), and (3) OVs are extremely immunogenic themselves and may distract the immune system from the tumor (34,45). To address aspects of these barriers, two innovative approaches have recently been developed.…”
Section: Engineering Oncolytic Vaccines To Prime or Boost Antitumor Imentioning
confidence: 99%
“…In that context, the immune suppressive nature of the tumor reflects the history of immune-mediated attack on the cancerous cells. It has been shown that immunotherapies cause further editing of the tumor and promote the outgrowth of tumor escape variants; 19,20 however, whether immunotherapies also influence the immune suppressive pathways in the tumor remains to be elucidated.…”
Section: Introductionmentioning
confidence: 98%